Experimental Scedosporiosis Induces Cerebral Oedema Associated with Abscess regarding Aquaporin-4 and Nrf-2 Depletions. (4th April 2019) - Ampawong, Sumate; Luplertlop, Natthanej
Abstract : Cerebral involvement especially brain abscess is life-threatening complication and major cause of death during Scedosporium apiospermum infection. However, little is known about pathogenesis of brain oedema associated with abscess in scedosporiosis. Experimental scedosporiosis was conducted in BALB/cMlac mice to characterize the presence of brain oedema, its type, and its related mechanisms focusing on aquaporin (AQP)-4, nuclear factor erythroid-2 related factor (Nrf-2), and tumor necrotic factor (TNF)- α . The results revealed that S. apiospermum infection induced severe inflammatory environment relevant to TNF- α expression and cytogenic oedema-associated brain abscess predominately in cerebrum of immunocompromised mice without voriconazole treatment reflecting to downregulation of AQP-4 in neighboring abscess areas and oedematous blood vessels. Downregulation of Nrf-2 in neuronal cells and myelin degeneration were significantly observed in nontreated mice. In summary, oxidative stress, severe inflammatory response, and space-occupying mass from abscess formation inducing tissue hypoxia might be the postulate causes of oedema induced by scedosporiosis.